The drivers of sustainable development in South African economy: The role of female advancement - Abiola John Asaleye; Kariena Strydom (Sustainable Futures)
Contemporary societies have challenges in achieving sustainable development, while African economies remain quite distant from this ideal course for sustainable growth. Likewise, official statistics in South Africa show a wide gap between male and female involvement in economic activities. Given this, the study investigates the connection between three dimensions of sustainable development and female advancement in South Africa using auto-regressive disturbed lags (ARDL), Structural Vector autoregressive (SVAR) and Ganger non-causality approach. The three dimensions of sustainable development considered in this study are economic, environmental and social, proxies by adjusted net national savings, carbon emissions and adjusted net national income per capita, respectively. The female advancement indicators are proxies by employment, wages and salaries, and secondary school enrolment. The result from the ARDL shows that female advancement indicators promote short (SR) and long-run (LR) economic sustainability. Also, female wages and salaries have a positive relationship with carbon emissions in the SR but not significantly in the LR. At the same time, female employment and secondary school enrolment have a positive relationship with carbon emissions in the SR but are negative in the LR. The primary causes affecting long-term environmental sustainability are GDP per capita, financial development, population density, trade openness and urbanisation. Also, female advancement indicators promote social sustainability, especially employment, wages and salaries. More so, the SVAR results show that the forecasting error shock of GDP has minimal effect on carbon emission with notable variation in the population density. The causality result shows a unidirectional relationship between economic sustainability and female secondary school enrolment, environmental sustainability and female secondary school enrolment, and social sustainability and female secondary school enrolment, all flowing to female secondary school enrolment. Based on the findings, the study recommended improving female educational standards and increasing involvement in economic participation.